Malignant Wolffian adnexal tumor in the ovary: a case report and literature review - Chi, Cheng; Li, Guoliang; Zheng, Zian; Wang, Xiangyu; Liu, Xiangyu (Frontiers in Oncology, 2025)
BackgroundWolffian adnexal tumor (WAT) is a rare neoplasm originating from the remnants of the Wolffian duct (mesonephric duct). Malignant WAT occurring in the ovary is exceptionally uncommon. This article presents a case of malignant WAT in the ovary, analyzing and discussing its histological features, diagnostic challenges, biological behavior, and treatment options in conjunction with relevant literature to enhance our understanding of this rare tumor.Case presentationA 64-year-old woman presented with an 8-month history of persistent abdominal pain and distension. An exploratory laparotomy revealed a small amount of pale-yellow ascites, a slightly atrophic uterus, and a left ovary without significant abnormalities. A solid mass measuring approximately 12 × 10 cm was observed between the left fallopian tube and ovary, displaying extensive dense adhesions to the posterior broad ligament and surrounding bowel. Frozen section pathology indicated a malignant tumor with necrotic areas suggestive of poorly differentiated carcinoma. The patient subsequently underwent a total hysterectomy, bilateral adnexectomy, omentectomy, pelvic lymphadenectomy, and pelvic adhesion release. Adjuvant chemotherapy with four cycles of paclitaxel and carboplatin (TC regimen) was administered, achieving normalization of tumor markers by the second cycle.ConclusionsWAT is a rare entity within the spectrum of female reproductive system tumors, predominantly benign in nature. Due to its extremely low incidence, standardized treatment protocols remain elusive. Further research is warranted to establish effective management strategies and provide a reference for future cases.